2011
DOI: 10.1186/1752-1947-5-156
|View full text |Cite
|
Sign up to set email alerts
|

Severe refractory autoimmune hemolytic anemia with both warm and cold autoantibodies that responded completely to a single cycle of rituximab: a case report

Abstract: IntroductionMixed warm and cold autoimmune hemolytic anemia runs a chronic course with severe intermittent exacerbations. Therapeutic options for the treatment of hemolysis associated with autoimmune hemolytic anemia are limited. There have been only two reported cases of the effective use of rituximab in the treatment of patients with mixed autoimmune hemolytic anemia. We report a case of severe mixed autoimmune hemolytic anemia that did not respond to steroids and responded to four weekly doses of rituximab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…Proteomics studies have demonstrated the presence of complements (C3, C4, and C9) in fibrillary GN and ITG [15]. The histological and molecular findings in the present case While no previous studies have demonstrated an association between ITG and cold agglutinins, nephrotic syndrome in patients with cold agglutinins has been found in the literature [9][10][11][17][18][19][20][21] (Table 3). In one case, a 66-year-old woman presented with CAD and nephrotic syndrome [9].…”
Section: Discussionsupporting
confidence: 46%
“…Proteomics studies have demonstrated the presence of complements (C3, C4, and C9) in fibrillary GN and ITG [15]. The histological and molecular findings in the present case While no previous studies have demonstrated an association between ITG and cold agglutinins, nephrotic syndrome in patients with cold agglutinins has been found in the literature [9][10][11][17][18][19][20][21] (Table 3). In one case, a 66-year-old woman presented with CAD and nephrotic syndrome [9].…”
Section: Discussionsupporting
confidence: 46%
“…and remained in remission for 1 year (with low dose steroids) at the time of reporting the case. Gupta and colleagues have also reported a case of complete remission of mixed AIHA (unresponsive to steroids) with a single course (four doses at weekly intervals) of rituximab . The patient remained in remission for 2 years at the time of reporting the case.…”
Section: Reviewmentioning
confidence: 97%
“…Th e patient did not require blood transfusions and her Hb level stabilized. Interestingly, the response reaction to RTX treatment varies, with patients responding to RTX after only a single cycle and others taking weeks or months to maximal response after 4 cycles [7,8]. Th e literature review suggested that patients with AIHA and CAHA can respond to re-treatment with RTX and durable responses can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RTX has been shown to be eff ective in the treatment of other autoimmune diseases associated with CAHA (rheumatoid arthritis), cold agglutinin acrocyanosis, viral infection associated nephropathy, cryoglobulinemia, hepatitis C infection, mixed AIHA [8,13,14].…”
Section: Discussionmentioning
confidence: 99%